The influence of Italian phonetics on vocal technique in classical and operatic singing - Nyiko Condry Ngobeni; Phindile Mpetshwa; Njabulo Sifiso Mthimkhulu (Cogent Arts & Humanities)
This study investigates the specific Italian phonetics that come into play in a discussion of Italian art song vocal technique in the areas of resonance, legato, diction, and expressivity. Adhering to principles of vocal pedagogy and phonetic theory, the research adopts a qualitative approach through a systematic review of relevant literature and performance-based studies to explore the interplay between phonetic components and vocal techniques. The findings show that Italian vowels, famed for their openness and clarity, amplify resonance, and my insertion helps with vocal projection. The consonants, for example, are distinct and allow for smooth, precise articulation of rolled ‘r’s, say, and open ‘l’s. These phonetic features enhance the technical precision of the playing and the music’s emotional expressiveness. The research underlines the importance of Italian phonetics as a basis for mastery in the bel canto tradition, which it presents as an essential area of vocal pedagogy. Nurturing the unique properties of Italian within vocal instruction can foster versatile and expressive singers who are well-versed in vocal technique and artistry.